Bezpośrednie i pośrednie formy inwestowania na rynku nieruchomości na przykładzie aktywności funduszy nieruchomości w Polsce - Śmietana, Katarzyna (Direct and Indirect Investment in The Real Estate Market on the Example of Real Estate Fund Activity in Poland, 2008)
The scale of investments made by institutional investors in the Polish real estate market is relatively small. In comparison with developed real estate markets the involvement of institutional inves- tors is limited by legal regulations, which impose limits of capital involvement, both in direct indirect real estate investments. Investment funds are becoming active investors in the Polish real estate market, however, the scale of direct investments made by these entities does not yet correspond with the activity manifested by this type of investors in the developed investment markets. With attention paid to the enormous significance of these entities for the investment market development, as well as the benefits given to minor investors by the possibility of indirect investment through funds, the following paper aims to present the legal bases of the activity, the assumptions of the investment policy and the form in which the aforementioned entities make their investments on the example of selected funds operating in the Polish real estate market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 558-568